[(3/4)^4 * (2/3)^-16]^-2
= [(3^4 / 4^4) * (2^-16 / 3^-16]^-2
= [(3^4 / 2^8) * (2^-16 / 3^-16]^-2
= [2^-24 3^20]^-2
= 2^48 3^-40
= 2^48 / 3^40
Answer:
B) 25°
Step-by-step explanation:
Assuming the quadrilateral is the one shown in the picture attached, then a triangle ADC is form, where m∠ADC = 125° and m∠1 = 30°. The addition of the three angles of a triangle is equal to 180°, so:
m∠ADC + m∠1 + m∠2 = 180°
Replacing with the known values and isolating m∠2 we get:
125° + 30° + m∠2 = 180°
m∠2 = 180° - 125° - 30°
m∠2 = 25°
Answer:the answer is 10 because if u subctract it will work
Step-by-step explanation:
Increased slowly, increased quickly